A Legal Comparison of Corporate Takeovers in the Digital Sector Under Competition Law in Indonesia and Germany - Fauzan Ervansyah; Hengki Firmanda; Samariadi (Melayunesia Law, 2026)
The digital economy and the rise of data-driven acquisitions challenge the effectiveness of conventional competition laws, which typically rely on physical asset parameters. This study aims to compare the legal frameworks for corporate takeover oversight in the digital sector between Indonesia and Germany. This research employs a normative legal method utilizing statutory and comparative approaches. The findings reveal fundamental differences and significant regulatory gaps. Indonesia still employs a post-merger notification system with thresholds strictly based on asset and revenue values. This conventional approach fails to detect strategic acquisitions of asset-light but high-valuation digital startups, leading to undetected data barriers. In contrast, Germany has successfully reformed its framework through the 10th Amendment to the GWB. Germany implements a pre-merger notification system alongside a transaction value threshold. This mechanism effectively captures startup acquisitions driven by strategic data control and future innovation potential rather than current revenue. The study concludes that Indonesia's current competition law is inadequate for the digital economy, and it is recommended that Indonesia adopt the transaction value threshold and transition to a pre-merger system to strengthen legal certainty.